Action monitoring fails when motor execution is too fast: no time for correction. Issue 3 (2021) - Ramdani, Céline; Sagui, Emmanuel; Schmid, Bruno; Castagna, Olivier; Davranche, Karen; Vidal, Franck
No abstract available